2011
DOI: 10.1111/j.1365-2125.2011.03945.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of combined treatment with praziquantel and albendazole in neurocysticercosis

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The antiparasitic drugs albendazole and prazoquantel have been used together before for geohelminths, echinococcosis and cysticercosis, but there is only scarce and discrepant data on the pharmacokinetics of these drugs when given together. WHAT THIS STUDY ADDS• This is a randomized, double-blinded, placebo-controlled phase II evaluation of the pharmacokinetics of albendazole and praziquantel in 32 patients with neurocysticercosis which demonstrates that combined alben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 27 publications
2
60
0
2
Order By: Relevance
“…Combinations of antiparasitic drugs, namely albendazole with praziquantel, have been anecdotally used, appear safe, and are likely associated with improved parasiticidal efficacy. [34][35][36] A second option reported in the literature is to increase the dose of albendazole up to 30 mg/kg/day, although the small numbers of treated patients do not yet allow conclusions regarding the safety of these regimes. 37,38 After appropriate pre-clinical work, human use of the veterinary drug oxfendazole may provide a more efficacious parasiticidal drug.…”
Section: New or More Recent Treatment Optionsmentioning
confidence: 99%
“…Combinations of antiparasitic drugs, namely albendazole with praziquantel, have been anecdotally used, appear safe, and are likely associated with improved parasiticidal efficacy. [34][35][36] A second option reported in the literature is to increase the dose of albendazole up to 30 mg/kg/day, although the small numbers of treated patients do not yet allow conclusions regarding the safety of these regimes. 37,38 After appropriate pre-clinical work, human use of the veterinary drug oxfendazole may provide a more efficacious parasiticidal drug.…”
Section: New or More Recent Treatment Optionsmentioning
confidence: 99%
“…Recent studies showed that the combination of praziquantel and albendazole increased the albendazole plasma concentration and therefore may improve the clinical outcome. 13 To control treatment-induced inflammation and therefore to reduce the likelihood of seizures we also started dexamethason treatment. [14][15][16] Conclusion NCC should be kept in mind in patients with a travel history to T solium endemic areas suffering from seizures associated with subcutaneous nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in mice showed a significant reduction of cysticerci after prolonged 20-and 25-day administration of albendazole (Zurabian et al 2013). In human medicine, the synergistic action of praziquantel and albendazole was employed to successfully treat infection (Garcia et al 2011;Fraga et al 2012;Anikpeh et al 2014). As for regular deworming of dogs, it is not effective against T. crassiceps cysticercosis, but may help to prevent contamination of the environment by tapeworm eggs contained in faeces of dogs parasitised by adult tapeworms in the intestine.…”
Section: Discussionmentioning
confidence: 99%